Improving Reading Ability of A Mentally Retarded Student Using The Picture and Picture Learning Method: A Single Case Study - Syafruddin Faisal Thohar (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
Every child is born with different abilities and potential in both academic and non-academic fields. This difference in potential is because not all children are born in perfect physical and mental condition or are called children with special needs (ABK). ABK require special attention and supervision, especially in receiving educational services. One group of ABK is children with mental retardation. The reading process for mentally retarded children involves complex cognitive processes, including the ability to remember, think, and reason. The aim of this research is to evaluate the effectiveness of the picture and picture learning method in improving reading skills in a student with mild intellectual disabilities at SLB X The research method is experimentation with a single case design. The intervention was implemented in 3 phases, namely baseline (A1), intervention, and baseline (A2) for 2 research subjects. Data were analyzed graphically to identify changes in reading ability. The results showed that both research subjects experienced significant improvements in reading ability after intervention. Reading scores increased from the first baseline to the second baseline. Picture and picture learning method has proven to be effective in improving reading ability and learning motivation of children with mild intellectual disabilities.